Fabrication of Cu4SnS4 Thin Films: Α Review - Ho, S. M. (Engineering, Technology & Applied Science Research, 2020)
Ternary compounds such as Cu4SnS4 thin films can be deposited onto glass substrates by various deposition methods: electrodeposition, chemical bath deposition, successive ionic layer adsorption and reaction, and evaporation techniques. Cu4SnS4 films could be used in solar cell applications because of their suitable band gap and large absorption coefficient. This paper reviews previous researches on Cu4SnS4 thin films. X-ray diffraction showed that the obtained films are orthorhombic in structure and polycrystalline in nature. Cu4SnS4 films exhibited p-type electrical conductivity and indicated band gap values in the range of 0.93 to 1.84eV.